Maternal serum levels of selected trace elements and heavy metals in pregnancies complicated by preterm prelabor rupture of membranes: A prospective and case-controlled study - Ali OVAYOLU; Nuray BOSTANCIERİ; Selver GÜLER; İlkay DOĞAN; Vugar Ali TÜRKSOY; Ali KOLUSARI (My University, 2021)
Aim: To measure maternal blood elements namely, aluminium (Al), antimony (Sb), arsenic (As), cadmium (Cd), chromium (Cr), cobalt (Co), copper (Cu), man- ganese (Mn), mercury (Hg), molybdenum (Mo), nickel (Ni), lead (Pb), tin (Sn), and zinc (Zn) in pregnant women complicated by preterm prelabor rupture of the membranes (pP-ROM) and to compare the results with healthy controls. Materials and Methods: Maternal blood levels of Al, As, Cd, Co, Cu, Cr, Hg, Mn, Mo, Ni, Pb, Sb, Sn, and Zn were evaluated in the pP-ROM group, which included 55 pregnant women complicated by pP-ROM and 60 healthy participants (control group) with respect to gestational weeks and maternal age. The maternal serum levels of trace elements and heavy metals in both groups were measured using inductively coupled plasma-mass spectrometry (ICP-MS) and compared. Results: 1o significant differences regarding gestational week, body mass index, gravidity, parity, and maternal age were observed p The mean serum whi- te blood cell level was higher in the pP-ROM group compared with the healthy controls (12.2±3.5 μL/mL vs. 10.1±2.6 μL/mL, respectively; p=0.001). The mean serum C-reactive protein level was higher in the pP-ROM group than in the he- althy group (0.99±1.47 mg/L vs. 0.40±0.27 mg/L, respectively; p=0.003). There were no differences in terms of mean maternal serum levels of Al, As, Cd, Co, Cu, Cr, Hg, Mn, Mo, Ni, Pb, Sb, Sn, and Zn between the study and control group p Conclusion: The selected trace elements and heavy metals in maternal serum are not involved in the pathogenesis of pP-ROM.
Keywords: Amniochorion; fetal membranes; metal exposure; pregnancy; premature birth; white blood cells